Lost Mansions
XII, 137 p.
Keywords: This provocative volume stimulates debate about lost 'heritage' by examining the history of the hundreds of great houses demolished in Britain and Ireland in the twentieth century. Seven lively essays debate our understanding of what is meant by loss and how it relates to popular conceptions of the great house.